2021
DOI: 10.1111/jdi.13647
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of severe non‐proliferative/proliferative diabetic retinopathy: More than a decade follow up in the Tehran Lipids and Glucose Study

Abstract: Aims/Introduction To examine the incidence rate of severe non‐proliferative and proliferative diabetic retinopathy (severe‐NPDR/PDR) and determine its potential risk factors. Materials and Methods The study consisted of 1,169 participants (675 women) with type 2 diabetes mellitus, aged ≥20 years. A trained interviewer collected information about the history of pan‐retinal photocoagulation as a result of diabetic retinopathy. Multivariable Cox proportional hazards regression models were applied. Results We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
(62 reference statements)
1
3
1
Order By: Relevance
“…However, our study did not find an independent association between hypertension and DR in multiple logistic regression analysis. This is in contrast to a recent study conducted in Iran 36 that reported prehypertension and newly diagnosed hypertension to be independent risk factors for PDR.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our study did not find an independent association between hypertension and DR in multiple logistic regression analysis. This is in contrast to a recent study conducted in Iran 36 that reported prehypertension and newly diagnosed hypertension to be independent risk factors for PDR.…”
Section: Discussioncontrasting
confidence: 99%
“…Cigarette smoking was found to be associated with PDR in our study. This is in agreement with the results from the recent study from Iran, 36 which found that being smoker increased the risk of PDR.…”
Section: Discussionsupporting
confidence: 93%
“…Blood samples were collected for fasting plasma glucose (FPG), 2-h post-load plasma glucose (2-hPG), total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and creatinine levels. The history of pan-retinal photocoagulation (PRP), which was carried out during the exposure period was considered as a surrogate for incident severe non-proliferative and proliferative diabetic retinopathy (NPDR/PDR) [ 22 ]. GFR was estimated by use of the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Clinically, PVD membranes exert a vitreoretinal traction which may lead to retinal detachment and are responsible for most of secondary retinal detachments following initial surgical repair. The incidence of PVD is expected to rise in the coming decades due to the increase of diseases and risk factors responsible for PVD development [4,[6][7][8][9][10][11][12]. However, surgical peeling of these membranes by specialized surgical teams remains the sole therapeutic option to this day, limiting patients' access to treatment and burdening healthcare systems.…”
Section: Introductionmentioning
confidence: 99%